2023
DOI: 10.1108/jhtt-12-2020-0319
|View full text |Cite
|
Sign up to set email alerts
|

Aspect-based sentiment analysis on online customer reviews: a case study of technology-supported hotels

Abstract: Purpose The purpose of this study is to determine the satisfaction of the guests who stay at hotels offering technology-supported products and services related to the services and products they receive by using the opinion mining technique. Design/methodology/approach In this research, 12,396 customer reviews on booking.com related to ten hotels belonging to a hotel chain using technology-supported products were evaluated with aspect-based sentiment analysis techniques. Findings As a result of this study, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 61 publications
0
17
0
Order By: Relevance
“…Therefore, this study suggests that fast-food restaurants should invest in training initiatives, including providing tutorials on the restaurant’s online ordering system, free Wi-Fi access and customer support for any technical issues (Mercan et al , 2021). In addition, fast-food restaurants should collaborate with customers to develop future digital technologies, ensuring that these technologies are requested and understandable by customers (Özen and Özgül Katlav, 2023). Second, this study found that the technology acceptance of fast-food restaurant customers affects hedonic and utilitarian values.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, this study suggests that fast-food restaurants should invest in training initiatives, including providing tutorials on the restaurant’s online ordering system, free Wi-Fi access and customer support for any technical issues (Mercan et al , 2021). In addition, fast-food restaurants should collaborate with customers to develop future digital technologies, ensuring that these technologies are requested and understandable by customers (Özen and Özgül Katlav, 2023). Second, this study found that the technology acceptance of fast-food restaurant customers affects hedonic and utilitarian values.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, digital technologies assist customers with orders quickly and enjoy their experience. Digital technologies also allow restaurants to promptly resolve customer concerns and worries (Özen and Özgül Katlav, 2023). As these benefits become evident, more fast-food restaurants will adopt digital technologies to stay competitive.…”
Section: Customer Technical Digital Transformation Readiness and Tech...mentioning
confidence: 99%
“…This research demonstrated the applicability of combining data mining and spatial clustering analysis as a tool to gain knowledge on the spatial pattern of the digital footprints of reputable tourist accommodation firms using Web-scraped STNSs data. Several studies have used tourism-and-hospitality-related UGCs for mapping geographic distribution and clustering (Kirilenko et al, 2019;Mou et al, 2020;Van der Zee et al, 2020). However, few of them analyzed the spatial clustering of the H&Rs based on online reputation and eminent digital footprints (Beneki and Spiggos, 2021;Guti errez et al, 2017;Gł owczy nski, 2022;Ye et al, 2018).…”
Section: Theoretical Implicationsmentioning
confidence: 99%
“…Online reputation has become an important contributor to the entrepreneurship and growth of T&H firms adopting e-tourism in their operations. Many tourism-and-hospitality-related UGC studies have focused on accommodations, destinations and attractions (Özen and Özgül Katlav, 2023; Ye et al , 2018). For instance, a survey of Google reviews found that pubs, restaurants and hotels are the local businesses with the most Google ratings, with 98.5% of restaurants and hotels having at least one Google review (BrightLocal, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, to the best of our knowledge, few studies have effectively modeled how different consumers assess multiple restaurant attributes differently. Moreover, the conventional text-mining approach ignores contextual information, such as surrounding words and word order; thus, it is challenging to extract textual information efficiently (Viñán-Ludeña and de Campos, 2022; Özen and Özgül Katlav, 2023).…”
Section: Introductionmentioning
confidence: 99%